Estimation of a minimum laser power with wavelengths of 1.47, 1.56, and 1.68 μm for efficient obliteration of varicose veins. (January 2022) - Ignat'eva, N.Yu.; Zakharkina, O.L.; Sviridov, A.P.; Mazaishvili, K.V.; Shekhter, A.B.
Abstract: Experiments modelling endovenous laser obliteration (EVLO) are performed. As a result, laser radiation powers P c at which collagen denaturation, tissue necrosis, and vasa vasorum destruction occur throughout the entire venous-wall thickness and, at the same time, the surrounding tissues are not subjected to unnecessary heating, are found. The main criterion for determining P c is the achievement of 100 % denaturation of venous-wall proteins, confirmed by morphological and calorimetric analysis. The P c values for laser wavelengths of 1.47, 1.56, and 1.68 μm are found to be 6.0 ± 0.2, 5.0 ± 0.2, and 6.0 ± 0.2 W, respectively. It is established for all wavelengths in use that the temperature of the external venous-wall surface reaches 91 ± 2 °C at the corresponding power P c . We relate the dependence of P c on the radiation wavelength to the formation of a coagulum on the optical fibre tip moving through a blood-filled vessel. The achievement of temperature necessary for coagulum formation is determined by the simultaneously occurring processes of energy absorption and its dissipation in the form of heat. These processes become more intense with an increase in the absorption coefficient of the medium. A mechanism is proposed to explain the relationship between the P c value and laser wavelength, based on the influence of the absorption coefficient of medium (blood) on the temperature near the fibre tip.